All you can ever know [compact disc, unabridged] - Chung, Nicole (HighBridge Audio, 2018)
Nicole Chung was born severely premature, placed for adoption by her Korean parents, and raised by a white family in a sheltered Oregon town. From childhood, she heard the story of her adoption as a comforting, prepackaged myth. She believed that her biological parents had made the ultimate sacrifice in the hope of giving her a better life, that forever feeling slightly out of place was her fate as a transracial adoptee. But as Nicole grew up; facing prejudice her adoptive family couldn't see, finding her identity as an Asian American and as a writer, becoming ever more curious about where she came from, she wondered if the story she'd been told was the whole truth.